Hubungan Antara Dukungan Emosional Keluarga Dengan Perilaku Remaja Pengguna Media Sosial Facebook - Yustika, Karenina Nuraini; Triyanto, Endang; Kusumawardani, Lita Heni (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2023)
Family emotional support is supported by feelings of security, comfort, and being loved by the family. The behavior of teenagers using social media on Facebook is an action that is usually carried out by someone who uses his Facebook account. This study aimed to determine the relationship between family emotional support and adolescent behavior using social media and Facebook. This study was a quantitative correlational study with a cross-sectional design. The number of respondents in this study was 48 students. , a Facebook user behavior questionnaire, and a Facebook usage behavior observation form. Data analysis using Sommers'd test. This study showed the same number of poor and good family emotional support (12.1%). There were ten respondents (17.2%) in the low category, thirty-six respondents (62.1%) in the medium category, and twelve respondents (20.7%) in the high behavior category. The relationship between family emotional support and the behavior of adolescent Facebook users (p = 0.004; p < 0.05; r = -0.259). There was a negative and weak relationship between family emotional support and adolescent behavior using social media and Facebook. This means that adolescents with good family emotional support will have low behavioral intensity in using Facebook social media. It is hoped that adolescents can obtain information from health workers about changes in adolescent development by health workers to help them by providing good emotional support for the family.